Ongoing Refinement and Innovation in the Data Collection Protocols of the Third Round of the National Social Life, Health, and Aging Project. (17th December 2021) - O'Doherty, Katie; Lawrence, Daniel; Wiencrot, Anna; Walsh, Sara; Satorius, Jennifer; Burgess, Erin; Sedlak, Lauren; Koepp, Kriston; Smith, Stephen
Abstract: Objectives: The third round (R3) of the National Social Life, Health, and Aging Project, a nationally representative, longitudinal survey of community-residing older adults, consisted of 4, 777 in-person interviews and 6, 100 completed visits to households to identify newly eligible respondents. It revisited respondents from the first rounds (Cohort 1), born in the years 1920 through 1947, and added new respondents (Cohort 2) born in the years 1948 through 1965. Coresidential romantic partners of both cohorts were also eligible. Data collection included in-person questionnaires, up to 11 biomeasures, and a self-administered, postinterview paper questionnaire. Methods: Questionnaire domains included social network and social support, elder mistreatment, physical health, cognitive function, romantic partners and sexuality, fertility and menopause, mental health, and employment and finances. Biomeasure collection included height, weight, waist circumference, blood pressure and heart rate, timed walk, balance, chair stands, smell, saliva passive drool in a tube (cortisol, dehydroepiandrosterone, estradiol, progesterone, testosterone), dried blood spots (C-reactive protein, Epstein–Barr virus antibodies, high-density lipoprotein cholesterol, hemoglobin, glycosylated hemoglobin [HbA1c], total cholesterol), and accelerometry (sleep patterns and physical activity). A brief questionnaire also collected data on respondents who were deceased or in too poor health to participate. Results: Measures such as response and cooperation rates are provided to evaluate the design and implementation. Discussion: This article describes innovation in the development and implementation of R3, the recruitment of a new cohort of respondents, and fidelity to prior rounds' study design and data collection procedures.